2015
DOI: 10.5367/ihe.2015.0244
|View full text |Cite
|
Sign up to set email alerts
|

University versus Practice

Abstract: This study aims to determine the skills shortages in first-year trainee accountants entering practice in South Africa and to recommend ways to address and overcome those shortages. Questionnaires were administered to registered audit firms in Gauteng Province to gather the perceptions of senior trainees, managers and partners on the skills shortages in first-year trainee accountants. The overall view was that universities did not equip first-year trainees sufficiently with the skills to be successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 26 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In addition, education providers can offer personalized learning according to learners' skill gaps and approaches to learning [58]. In line with that, many articles emphasize the importance of practice-oriented, hands-on, interactive learning experiences, such as learning factories, work-integrated learning programmes, and workbased learning [40,42,55,56,59,60] by e.g., apprenticeships, hands-on workshops on trending topics becoming more important in the company and participation in online training [29]. However, [46] points out that education shouldn't be too narrowly tailored to prepare for certain job workplaces or jobs since it makes the use of this particular education quite inflexible.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, education providers can offer personalized learning according to learners' skill gaps and approaches to learning [58]. In line with that, many articles emphasize the importance of practice-oriented, hands-on, interactive learning experiences, such as learning factories, work-integrated learning programmes, and workbased learning [40,42,55,56,59,60] by e.g., apprenticeships, hands-on workshops on trending topics becoming more important in the company and participation in online training [29]. However, [46] points out that education shouldn't be too narrowly tailored to prepare for certain job workplaces or jobs since it makes the use of this particular education quite inflexible.…”
Section: Resultsmentioning
confidence: 96%
“…Stakeholders' expectations regarding which professional skills accounting graduates should possess have been widely investigated (Abayadeera & Watty, 2014;Jackling & Watty, 2010;Naidoo, Jackling, Oliver & Prokofieva, 2011) but limited research has been done on their technical knowledge expectations (Barac, 2009c;Joubert et al, 2009). It was however reported that graduates are unable to apply their technical knowledge in practice (Van Romburgh & Van der Merwe, 2015). Below follows a summary of previous research relating to the various accountancy-focused subject areas and courses, including financial accounting and reporting, taxation and audit and assurance.…”
Section: Previous Researchmentioning
confidence: 99%
“…The ITC is written at the completion of aspiring professional accountants' education programmes, at the start of trainee accountants' practical training programmes SAICA, not dated b;SAICA, 2014) at registered training offices. These training offices can either be at audit firms, classified as small, medium or large audit firms, or at companies in commerce and industry (Barac, 2009b;Van Romburgh & Van der Merwe, 2015). The Framework Summary of Detailed Guidance for the Academic Programme is used by educators to identify those competencies that trainee accountants entering into their training programmes should already have mastered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to teaching accounting rules and concepts, educators need to improve practical skills so as to help students understand and remember rules better. It will also facilitate the achievement of other goals of accounting education, such as developing thinking skills, communication and problem-solving skills, and the ability to learn lifelong [13].…”
Section: Introductionmentioning
confidence: 99%